Los valores religiosos y la laicidad de la esfera pùblica (Stato, Chiese e pluralismo confessionale, 2013)
Il contributo, che riproduce il testo della Relazione al Convegno: Laicidad y Libertad religiosa, Universidad Panamericana (Instituto de Investigaciones Jurìdicas, UNAM, Ciudad de Mexico, 20-21 febbraio 2013), è stato accettato dal DirettoreSOMMARIO: 1. La laicidad es un problema cultural, no politico - 2. La esfera pública y su neutralidad - 3. La razón religiosa y la razón secular en la esfera pública - 4. La esfera pública y los valores públicos.Abstract:The concept of secularism can be understood in a political perspective or in a legal one. However, secularism is frequently identified with the concept of neutrality, so committing an epistemological error. In this essay, I try to demonstrate that the religious logos is indistinguishable from secular reason, and they both have the same dignity in the public debate. Finally, the article seeks to demonstrate that secularism in pluralistic societies, requires the cooperative research of the valuesinherent in social practices, in a perspective that is neither relativistic nor ideological.Key words: Secularism, neutrality, objectivity.
Keywords: Laicità e pluralismo